Health-related quality of life in health states corresponding to different stages of perianal fistula associated with Crohn’s disease: a quantitative evaluation of patients and non-patients in Japan - Masafumi Kato; Mariko Yoneyama-Hirozane; Katsuhiko Iwasaki; Mao Matsubayashi; Ataru Igarashi (Journal of Market Access & Health Policy)
ABSTRACTBackground Perianal fistula (PF), a complication of Crohn’s disease (CD), affects health-related quality of life (QOL).Objective To elucidate QOL of health states corresponding to different stages of PF associated with CD in Japan.Method This cross-sectional, observational, web-based questionnaire survey assessed eight different health states in patients with CD and PF and individuals without CD (non-patients) from the Medilead Healthcare Panel (MHP) and determined the utility values (QOL scores) in each health state by the time trade-off method. In patients, we determined also the utility value of the current health state associated with CD and the PF. The analysis excluded respondents with logical inconsistencies.Results The analysis included 82 patients and 576 non-patients with the same sex and age distribution as the Japanese population. In both groups, mean utility values were higher in remission (patients, 0.78; non-patients, 0.51) than in non-remission states, with lowest values for poor prognosis after proctectomy (patients, 0.13; non-patients, −0.10) and highest values for the state with mild symptoms (patients, 0.60; non-patients, 0.30). In patients, the mean utility value of the current health state was 0.71.Conclusion QOL decreases with increasing severity of PF and is lower for good prognosis after proctostomy than for remission.